A adesão dos municípios na implementação do Programa Nacional de Alimentação Escolar: uma análise exploratória no Sudoeste Paulista - Lopes Junior, Edmilson Carlos de Almeida (Universidade Federal de São Carlos, 2021)
The National School Feeding Program, responsible for feeding more than 40 million schoolchildren across the national territory, defined, in 2009, a mini-mum of 30% of all resources transferred to states and municipalities by the Na-tional Education Development Fund for the purchase of food produced by fam-ily farmers, with the aim of promoting the development of that category at a lo-cal level. However, the program has faced operational barriers. Twelve years after the implementation of Law 11.947/2009, many municipalities are still un-able to reach the minimum values, and many other even do not acquire any value. This work purposes to identify conditioning factors of the adherence to the purchase of family agriculture by the municipalities. To this end, we divided the work into article-chapters, trying to understand the various spheres of the execution of the program. The first article presents a history of changes in the legal regulatory framework since the implementation of Law 11.947/2009, seek-ing to understand how they allowed, or not, the greater applicability of the law. The second article provides an overview of the program's execution in the state of São Paulo, using the intermediate regions and municipalities of the state as a spatial reference, where an exploratory analysis of the influence of the pres-ence of family farming in the region and the size of the municipalities is carried out. Finally, the third article conducts an exploratory analysis of the construc-tion of public calls in the São Paulo's Southwest region, identifying the tech-nical challenges of preparing this purchase instrument. This work made it pos-sible to identify constraints and obstacles to the applicability of the purchase of foodstuffs from family farming and to design a research agenda for the analy-sis of state capacities in the application of school income as a tool to promote family farming.
Adherence of municipalities in the implementation of the National Program for School Food: an exploratory analysis in the Southwest of São Paulo
Keywords: Agricultura familiar; Desenvolvimento Rural; Alimentação Escolar; Family farming; Public policies; School meal; CIENCIAS HUMANAS::CIENCIA POLITICA::POLITICAS PUBLICAS::ANALISE INSTITUCIONAL